Time-course of changes in performance, biomechanical, physiological and perceptual responses following resistance training sessions - Naves De Oliveira Goulart, K.; Resende, N. M.; Drummond, M. D. M.; Oliveira, L. M.; Lima, F. V.; Szmuchrowski, L. A.; Fujiwara, R. T.; Pena Couto, B. (European Journal of Sport Science, 2021)
This study determined the time-course of recovery after resistance training (RT) sessions and the association between changes in performance with changes in biomechanical, physiological and perceptual parameters. After a 4-week familiarization period, 14 resistance-trained males performed 3 experimental conditions, each one including 2 sessions with a recovery interval of 24, 48 h or 72 h, in a randomized order. RT sessions consisted of 5 sets of 8-10RM on squat and leg press exercises. The resistance was equal for the 2 sessions of each condition and repetitions were performed until concentric failure. Volume load (VL) and first set volume load (FSVL) were compared between sessions. Tests before each session included countermovement jump (CMJ), maximal voluntary isometric contraction (MVIC), creatine kinase (CK) and delayed onset muscle soreness (DOMS). (2 × 3) ANOVA with effect sizes (ES) assessed the time-course of recovery and Kendall test the correlation between variables (a = 0.05). Significant interaction was observed for all variables, except for CK, where a condition main effect occurred. Comparisons between post and pre-intervals showed VL (p = 0.011;ES = -0.90) decreased for 24 h condition, while FSVL remained decreased for 48 h (p = 0.031;ES = -0.63) and DOMS increased (p = 0.001;ES = 3.52). CMJ (p = 0.025;ES = 0.25) and MVIC (p = 0.031;ES = 0.14) performance increased at 72 h. FSVL (r = 0.424), CMJ (r = 0.439), MVIC (r = 0.389) and DOMS (r = -0.327) were significantly correlated with VL (p < 0.05). Time-course of VL showed the necessity of at least 48 h for the reestablishment of performance, though better perceptual responses were evident at 72h. Thus, both recovery intervals may be beneficial after lower-limbs RT until concentric failure, though chronic effects still need to be investigated.